ROLE OF ELECTRONIC INSTRUMENTS IN TEACHING AND DEMONSTRATION: शिक्षण एवं प्रदर्शन में इलेक्ट्रॉनिक वाद्यों की भूमिका - Singh, Soumya (International Journal of Research -GRANTHAALAYAH, 2015)
The construction of nad based on the Vedic concept is first an expression of God. Amarkar was considered as Brahmnad since primitive times. Today's music has resulted from human efforts in its present form. Change is the law of nature and this change is also seen in our classical music which has left a positive and negative impression somewhere. In this sequence, the role of electronic instruments in music teaching and performance has been very important. वैदिक अवधारणा के आधार पर नाद का निर्माण सर्वप्रथम ईश्वर की अभिव्यक्ति है। आदिम काल से ही अ¨ऽमकार क¨ ब्रह्मनाद माना गया। आज का संगीत मनुष्य के प्रयत्न¨ं से अपने वर्तमान रूप में परिणित हुआ है। परिवर्तन प्रकृति का नियम है अ©र यही परिवर्तन हमारे शास्त्र्ाीय संगीत में भी दिखता है जिसने कहीं सकारात्मक त¨ कहीं नकारात्मक छाप छ¨ड़ी है। इसी क्रम में संगीत शिक्षण एवं प्रदर्शन में इल्¨क्ट्रॉनिक वाद्य¨ं की भूमिका बहुत अहम रही हैं।